Kajian Literatur tentang Dimensi Lengkung Gigi Fase Gigi Bercampur pada Anak Laki-Laki dan Perempuan - Puspita Hadi; Ryna Dwi Yanuaryska; Sri Kuswandari (Jurnal Syntax Admiration, 2024)
The tooth growth phase starts from the age of 6 years with the first molar growth, this is a reference to assess the need for space and the possibility of malocclusion in adulthood. The dimension of the tooth arch is important in orthodontic treatment in children, especially in the mixed teeth phase because it will affect the treatment plan. The dimensions of the tooth arch are affected by various factors such as tooth eruption, genetics, growth patterns, environment and ethnicity. This study is a Literature Review using secondary databases from Google Scholar, Science Direct and Pubmed with the keywords "Dental Arch Dimension AND mixed dentition", "Gender AND Mixed Dentition" and "Children AND Dental Arch Dimension" which have been carried out previously domestically and abroad. Based on the results of the screening, 15 articles were obtained that met the criteria. In the study, 10 non-specific articles were found to discuss the dimensions of tooth arch in boys and girls in the mixed tooth phase. The five selected articles showed significant differences between sex, age, and race that affected the length and dimensions of the tooth arch in this phase. However, some studies have also shown that the differences are not significant in certain age ranges and races. In conclusion, The mixed tooth phase is an important period in the growth of a child's dental arch, where differences in the size of the tooth arch can be seen between different racial or ethnic groups. Gender also plays a role in determining the dimensions of the tooth arch, which affects the orthodontic treatment plan.